Systematic Review: Faktor-Faktor Resiliensi Individual pada Dewasa Awal yang Mengalami Childhood Abuse - Ingelina, Budi; Satiadarma, Monty P.; Soetikno, Naomi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
Child abuse or violence against children is not a new phenomenon that occurs in societies around the world. This phenomenon has also been happening in Indonesia for a long time. Some people still consider physical violence against children by parents or caregivers to be normal as a way to educate and discipline children. However, the negative impact on children who experience violence during childhood may only become apparent later when the child enters early adulthood. Resilience is found to tend to be negatively related to the experience of adversities in childhood. Resilience factors can contribute to reducing the damaging effects of childhood abuse, as well as helping young adults to be able to process the adversities they experienced in childhood. For this reason, researchers wanted to investigate resilience factors in early adults who experienced childhood abuse by integrating the findings of studies on childhood abuse and resilience published from 2013 to 2022. This research uses the systematic review method by searching research data on four sources: APA Psycnet, PubMed, ScienceDirect, and Wiley Online. Based on the results of data searches, researchers found more than 6000 articles and after going through strict filtering, 5 articles remained that were closely related to this research. Individual resilience factors were researched more frequently than family and community factors in those 5 articles. This study concluded that individual resilience factors have different characteristics, and some can influence others.